'Green' surface treatment for water-repellent cotton fabrics. Issue 1 (March 2016) - Zhong, Yidong; Netravali, Anil N.
Abstract : An environment-friendly 'green' method to obtain water-repellent (hydrophobic) cotton fabrics has been developed. Aliphatic fatty chains were grafted onto cotton (cellulose) fiber surface to decrease the surface energy and, thus, obtain water repellency. A benign accelerator was used to facilitate the reaction between fatty acids and cellulosic hydroxyl groups. Microwave heating, an energy-efficient method, was used to reach the reaction temperature. Fatty anhydride, considered to have a higher reactivity than fatty acids, was initially prepared. This process was monitored using high-performance liquid chromatography and attenuated total reflectance-Fourier transform infrared (ATR-FTIR) techniques. The effects of fatty acid chain length as well as microwave heating parameters on the hydrophobicity of the cotton fabrics were studied. The resulting hydrophobic cotton fabrics were characterized by water contact angle, laundry durability test, tensile test, and ATR-FTIR spectroscopy. The green method developed here resulted in a hydrophobic cotton fabric with a water contact angle of over 137° (± 3°). Further, the hydrophobicity was shown to be permanent and lasted for 37 cycles of laboratory laundry washes (equivalent to over 185 regular washes). ATR-FTIR results confirmed the grafting of fatty acids on cotton fabrics.